Pendidikan dan Paritas terhadap Pemakaian Alat Kontrasepsi Bawah Kulit (AKBK) - Lia Hartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the relationship between education and parity with the use of Under-the-Skin Contraceptives (AKBK) in Ermi's Independent Practice Midwives (BPM), Karya Bakti, 2020. This research method uses an analytical survey method with a cross sectional approach. The results of univariate analysis obtained from 98 respondents showed that there were 35 mothers (35.7%) who used AKBK contraception and 63 people who did not use AKBK contraception (64.3%). Most of the mothers with less education were as many as 64 people (65.3%), and mothers with good education were 34 people (34.7%). And most of the mothers had low parity (having children <3) as many as 60 people (61.2%), and mothers with high parity were 38.8%. Based on the results of the chi square statistical test on education, it was found that ρ value was 0.00 and ρ value on maternal parity was 0.00. In conclusion, there is a significant relationship between education and maternal parity on the use of contraceptives under the skin. Keywords: Parity, Use of Under the Skin Contraceptives (AKBK), Education